0086 Novel Use Of Simulation In Mental Health Education. (1st November 2014) - Jabur, Zainab; Cross, Sean; Pathan, James; Wilson, Catherine; Tritschler, Chris; Campbell, Lloyd; Luff, Adrian; Reedy, Gabriel
Abstract : Background: In other fields of medicine, simulation training has become increasingly recognised as a useful tool for teaching on a wide range of subjects that highlight both technical and non-technical skills. However, simulation for psychiatry education is not widely reported in the literature. Methodology: Our centre has designed and delivered a programme of simulation-based interventions to multi-disciplinary mental health professionals, using a combination of high and low fidelity simulation approaches, including mannequins, actors, and props. The courses address different aspects of clinical care for psychiatric patients, including: Acute medical care for the psychiatric patient (centre- and in-situ based) Interacting with legal tribunals and coroner's courts Assessing risk and clinical decision making Emergency psychiatry We are also developing unique models of debriefing that are better suited to mental health simulation. This presentation will report on these innovative courses and on our experiences designing and delivering them. We will explore the unique technical challenges and nuances of working with actors in mental health simulation. Results/outcomes: In the last two years, our centre has trained more than 300 staff members in more than 10 newly developed courses. Our initial evaluation data shows: statistically significant increase in knowledge around the management of self-harm and risk assessment significant increase in awareness around the process of decision making and insight into personal and systemic bias significant increases in confidence around management of health at the mental/physical divide Potential impact: The courses have been very well-received and popular, with word-of-mouth feedback continuing to increase demand. As such, our centre aims to continue to expand and develop this programme to further serve other professionals who regularly encounter mental health issues. We are continuing to evaluate these innovative courses and are preparing to submit many of them for peer-reviewed publication to share them more widely. References: Subodh D. Simulation in psychiatric teaching. Advances in Psychiatry Treatment 2012;18:292–298 Thomson AB, Cross S, Key S, et al . How we developed an emergency psychiatry training course for new residents using principles of high-fidelity simulation. Med Teach 2013;35(10):797–800